Prevalence of insomnia symptoms and associated risk factors in UK Biobank participants with hazardous alcohol use and major depression. (1st December 2021) - Kolla, Bhanu Prakash; Biernacka, Joanna M.; Mansukhani, Meghna P.; Colby, Colin; Coombes, Brandon J.
Abstract: Introduction: We aimed to examine the prevalence of insomnia symptoms (IS), sleep duration, and associated risk factors in participants with hazardous/harmful alcohol use (HAU), major depressive disorders (MDD), and HAU+MDD. Methods: Data from the UK Biobank (UKB) (n = 55, 000) were utilized to categorize participants into those with MDD (n = 5612), HAU (n = 15, 893), MDD+HAU (n = 3738), and controls (n = 29, 511). We examined whether rates of IS and sleep duration differed among the groups and determined the clinical predictors of IS. Rates of IS and sleep duration were compared using regression analyses accounting for demographic (age, sex, ethnicity, Townsend deprivation index) and clinical (body mass index, neuroticism score, alcohol consumption) factors. Results: The unadjusted prevalence of IS was 26.5%, 27%, 39.5%, and 43% in control, HAU, MDD, and MDD+HAU categories respectively. Rates of IS in controls versus HAU and MDD versus MDD+HAU did not differ in unadjusted models (p = 0.45 and 0.075, respectively). Prevalence of IS differed in the four groups (p < 0.0001 for all pairwise comparisons) after adjusting for demographic confounders. After further adjustment for clinical factors, effect sizes were reduced, but pairwise comparisons remained significant. After adjusting for demographic and clinical factors, sleep duration did not differ among the groups. After accounting for diagnostic category and demographic/clinical factors, older age (OR=1.33 per 10 year increase; p < 0.0001), female sex (OR=1.39; p < 0.0001), obesity (OR=1.17 compared to normal; p < 0.0001), higher neuroticism score (OR=1.13; p < 0.0001), and alcohol consumption (OR=1.01 per serving increase; p < 0.0001) were associated with IS. Conclusion: Sleep-related morbidity is the greatest in the MDD+HAU group, followed by the MDD group. Demographic and clinical characteristics explain some, but not all of the differences in the prevalence of IS in MDD±HAU. Genetic and other factors capable of influencing IS in those with MDD, HAU, and MDD+HAU merit future investigation. Highlights: This is the first study to examine the prevalence and correlates of sleep disturbance in a sample with HAU±MDD. Prevalence of insomnia symptoms was greatest in those with hazardous alcohol use and major depressive disorder. Clinical and demographic factors associated with insomnia symptoms were similar across all conditions. The lower prevalence of insomnia symptoms in subjects with HAU was likely secondary to the over representation of younger men.